Constitutive model and permeation evolution characteristics of mudstone-slag-based waterproofing composites considering cyclic damage - Wang, Guilin; Chen, Yuanguang; Cao, Xinfeng; Kong, Lingyao; Zhang, Yafei (Frontiers in Earth Science, 2025)
To address the need for minimal permeability and adequate strength in the reconstructed aquiclude of open-pit coal mine waste dumps, we formulated a mudstone-slag-based waterproof composite (MSWC), incorporating mudstone, slag, waste rock, and an alkaline catalyst. Initial cyclic damage was emulated using uniaxial cyclic loading and unloading (UCLU), after which we conducted a series of tests on the MSWC, including penetration, uniaxial compression, SEM, and CT scans, to assess the impact of varying degrees of initial cyclic damage. We explored the MSWC’s mechanical attributes, stiffness, permeability, and pore structure across a range of UCLU cycles (N) and developed a damage constitutive model to interpret the damage parameters. Our findings indicate that as N cycles escalate, there is a marked exponential reduction in the MSWC’s uniaxial compressive strength, and stiffness. This is attributed to the progressive enlargement of microcracks and pores within the material, leading to a reduction in its overall strength. Specifically, the uniaxial compressive strength (UCS) dropped by 6.56%, 13.13%, and 16.49%, the stiffness by 9.46%, 12.43%, and 19.73%, and porosity rose from 1.62% to 2.31%, 2.56%, and 2.67%. Consequently, the MSWC is deemed suitable for use as an aquiclude and can be effectively implemented in such applications. These findings offer valuable insights for the ecological rehabilitation of open-pit coal mine waste dumps.